Higher Education in Europe 2009 Developments in the Bologna Process (Education, Audiovisual and Culture Executive Agency, 2009)
This report takes a partial look at the emerging European Higher Education Area (EHEA). It is partial in two ways the selection of topics for consideration, and the type of information gathered for analysis.